2018
DOI: 10.1021/acs.energyfuels.8b01958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of H2 Enrichment and Inlet Velocity on Stability Limits and Shape of CH4/H2–O2/CO2 Flames in a Premixed Swirl Combustor

Abstract: The stability characteristics of swirl-stabilized hydrogen-enriched CH4–O2–CO2 premixed flames were experimentally investigated to determine the effects of hydrogen addition and inlet velocity on flame stability under stoichiometric conditions (φ = 1.0). The stability limits in terms of blowout and flashback were identified over wide ranges of hydrogen fraction (HF: %H2 in H2–CH4 mixture) and oxygen fraction (OF: %O2 in O2–CO2 mixture) at fixed inlet velocity of 6 m/s. The lines of stability limits were plotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…The blowout limit of the present stratified hydrogen-enriched oxy-methane combustor is plotted in Figure against HF–OF coordinates, i.e., the limit describes the minimum HF needed to sustain the primary CH 4 /O 2 /CO 2 flame at a given OF (level of CO 2 dilution). The square symbols in Figure a represent the stratified limit (H 2 –CH 4 /O 2 /CO 2 ) of the present study, whereas the triangular symbols depict the fully premixed limit (CH 4 /H 2 /O 2 /CO 2 ) of Hussain et al The first observation to make is that hydrogen enrichment generally improves the blowout limit, as expected. , Similar to the fully premixed case of Hussain et al, enriching the present oxy-methane flame with stratified H 2 allows for reaching higher levels of CO 2 dilution (OF = 17.7% at HF = 68.8%), compared to the nonenriched flame (HF = 0%), which blows out at OF = 23%. The present study thus recommends hydrogen enrichment as a general effective solution to improve the blowout stability of oxy-fuel flames and reduce their carbon footprint while not affecting the exhaust composition (CO 2 + H 2 O) for cost-efficient carbon capture.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The blowout limit of the present stratified hydrogen-enriched oxy-methane combustor is plotted in Figure against HF–OF coordinates, i.e., the limit describes the minimum HF needed to sustain the primary CH 4 /O 2 /CO 2 flame at a given OF (level of CO 2 dilution). The square symbols in Figure a represent the stratified limit (H 2 –CH 4 /O 2 /CO 2 ) of the present study, whereas the triangular symbols depict the fully premixed limit (CH 4 /H 2 /O 2 /CO 2 ) of Hussain et al The first observation to make is that hydrogen enrichment generally improves the blowout limit, as expected. , Similar to the fully premixed case of Hussain et al, enriching the present oxy-methane flame with stratified H 2 allows for reaching higher levels of CO 2 dilution (OF = 17.7% at HF = 68.8%), compared to the nonenriched flame (HF = 0%), which blows out at OF = 23%. The present study thus recommends hydrogen enrichment as a general effective solution to improve the blowout stability of oxy-fuel flames and reduce their carbon footprint while not affecting the exhaust composition (CO 2 + H 2 O) for cost-efficient carbon capture.…”
Section: Resultssupporting
confidence: 71%
“…Increasing HF was generally observed to improve the reaction kinetics in the reaction zone, leading to shorter and more compact flames. The stability limits were reported to be independent of adiabatic flame temperature, which was also confirmed by Abdelwahid et al 18 Araoye et al 19,20 reported that hydrogen enrichment enhances the combustor turndown by shifting the blowout limit to leaner conditions. It was proven that the stabilizing effect of hydrogen is entirely a reaction-kinetics effect and cannot be attributed to hotter flames; i.e., the reactions are controlled by the laminar burning rate.…”
Section: Introductionsupporting
confidence: 62%
“…Research shows that enriching hydrocarbon fuels with H 2 reduces the rates of NO x , CO, and soot formation. , It has been reported that adding H 2 suppresses the surface growth rate of soot, , in addition to reducing aldehyde emissions because of the reduction in CH 2 O and CH 3 CHO formation rates . H 2 enrichment also broadens the flammability limits; , LBO can be deferred with H 2 addition in GTs . The characteristics, both instantaneous and average, of turbulent premixed flames can be influenced significantly by H 2 enrichment.…”
Section: Fuel-flexible Combustion In Gas Turbinesmentioning
confidence: 99%
“…24,25 Several studies showed that H 2 addition can reduce the soot formation and lower the generation of CO in the combustion. 26−29 In addition, it can increase the laminar flame speed, 30 extend the range of flammability limits, 31 and improve the turbulent flame speed. 32 In the study by Imteyaz et al, 24 the stability map of H 2 -enriched oxy-methane flames in a swirl-stabilized model gas turbine combustor were determined over a range of hydrogen fraction (HF).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research in combustion indicates that hydrogen addition with conventional fuel in combustion can be beneficial in terms of overcoming combustion instabilities, increasing operability limits and reducing NOx emission . Because of the better performance in combustion, hydrogen enriched fuels like syngas and other hydrogen blends are being considered as an alternative to the natural gas. , Oxy-combustion with premixed fuel-oxidizer supply can benefit greatly from H 2 -enriched fuels. , Several studies showed that H 2 addition can reduce the soot formation and lower the generation of CO in the combustion. In addition, it can increase the laminar flame speed, extend the range of flammability limits, and improve the turbulent flame speed . In the study by Imteyaz et al, the stability map of H 2 -enriched oxy-methane flames in a swirl-stabilized model gas turbine combustor were determined over a range of hydrogen fraction (HF).…”
Section: Introductionmentioning
confidence: 99%